Historiography question relationship zaporozh and don Cossacks (the end of XV - beginning of XVIII c.) at the turn of XIX-XX centuries - Giria, Kateryna (Skhid, 2013)
In the given article the author using material of historiographic sourses views the development of historiography of Ukrainian-Don correlations (the end of XVth - the beginning of XVIIIth cent.) from the end of ХІХ till the beginning of ХХ c. This article has been depicted on the base of the complex analysis of the works by Ukrainian and Russian authors from the end of ХІХ th till the beginning of the ХХ th cent. The main aspects of research of this problem in the Russian and Ukrainian historiography have been depicted. The peculiarities of showing of the correlations between Zaporozh and Don Cossacks in historical literature have been analysed, the contribution of different authors at the investigations of the given problem has been shown. Author has depicted the results of investigations of the correlations between Zaporozh and Don Cozzacks on the given period of development of historiography.